Ovarian tumors - epidemiology, diagnosis and prevention in Poland - Ulenberg, Agata; Ulenberg, Grzegorz (Journal of Education, Health and Sport, 2018)
Ovarian cancer is one of the deadliest diseases plaguing women today. Morbidity and mortality is drastically high and unfortunately still growing. In many cases, the medicine is powerless. The very term cancer awakens in us the fear, uncertainty and significantly increases the level of stress. The disease is an element of human life, it is a drama for the patient and his family. For a time, completely changes the man and his subordinates pobytom life in the hospital and the next stages of therapy.The aim of this work is to present the problems associated with the occurrence of ovarian tumors. Presentation of ways of early diagnosis which can significantly increase the survival rate of women suffering.The work shows how serious problem in modern gynecological oncology is constantly ovarian cancer. It is characterized by very high mortality rate among cancers of the female genital.